Enhancing Security and Efficiency In Cloud Computing Users Using Multi-keyword Ranking Model - Manimalathi, SM; Senthilkumar, A (International Journal of Computer Sciences and Engineering, 2025)
The venture defines and understand the issue of multi-catchphrase positioned seek over scrambled cloud Information (MRSE) while saving strict framework insightful assurance in the cloud processing paradigm. Information proprietors are motivated to outsource their complex Information administration frameworks from neighborhood sites to the business open cloud for awesome adaptability and monetary savings. But for ensuring Information privacy, delicate Information have to be scrambled before outsourcing, which obsoletes customary Information usage based on plain content catchphrase search. Thus, enabling a scrambled cloud Information seek administration is importance. Considering the vast number of Information clients and archives in the cloud, it is vital to allow numerous catchphrases in the seek demand and return archives in the request of their significance to these keywords. Related works on searchable encryption center on single catchphrase seek or Boolean catchphrase search, and rarely sort the seek results. Among diverse multi-catchphrase semantics, choosing the proficient likeness measure of “coordinate matching,” i.e., as numerous matches as possible, to catch the significance of Information archives to the seek query. Specifically, here use the “internal item similarity” i.e., the number of inquiry catchphrases appearing in a document, to quantitatively assess such likeness measure of that archive to the seek query. Amid the file construction, each archive is related with a twofold vector as a sub file where each bit represents whether relating catchphrase is contained in the document. The seek inquiry is too depicted as a twofold vector where each bit implies whether relating catchphrase appears in this seek request, so the likeness could be precisely measured by the internal item of the inquiry vector with the Information vector. However, straightforwardly outsourcing the Information vector or the inquiry vector will damage the file assurance or the seek privacy.